Methods for microeconometric risk and vulnerability assessments - Hoddinott, John F.; Quisumbing, Agnes R. (World Bank, 2003)
This "toolkit" provides quantitative tools to practitioners who want to undertake risk and vulnerability assessments using household data. While one could use price, exchange rate, and balance of payments data to examine macroeconomic shocks, and rainfall data to assess the severity of droughts and floods, we are ultimately interested in their impacts on households - thus the emphasis on household data." -- Back Cover